2013
DOI: 10.1007/s00246-013-0830-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia in Children After Cardiac Surgery

Abstract: Ventilator-associated pneumonia (VAP) is a nosocomially acquired infection that has a significant burden on intensive care units (ICUs). We investigated the incidence of VAP in children after cardiac surgery and its impact on morbidity and mortality. A prospective cross-sectional review was performed in the postoperative cardiac patients in pediatric cardiac intensive care unit (PCICU) patients from March 2010 until the end of September 2010. The patients were divided into two groups: the VAP group and the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…Also, the role of nutrition dosing has been questioned, and untoward effects of early EN were not restricted to patients receiving the highest energy doses 33 . No data are available in the pediatric age, although small studies have suggested that PN is associated with higher ventilator‐associated pneumonia and bloodstream infection 34 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the role of nutrition dosing has been questioned, and untoward effects of early EN were not restricted to patients receiving the highest energy doses 33 . No data are available in the pediatric age, although small studies have suggested that PN is associated with higher ventilator‐associated pneumonia and bloodstream infection 34 …”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for ventilator-associated pneumonia were PRISM III score > 10 and transfusion of fresh-frozen plasma. 12 Epidemiology of perioperative infections in low-and middle-income countries Among 21 studies in low-and middle-income countries, four were conducted in China, [43][44][45][46] four in India, [47][48][49][50] three in Brazil, [51][52][53] two in Saudi Arabia 54,55 , and one each in Argentina, 56 Bosnia Herzegovina, 57 Iran, 58 Ethiopia, 59 Guatemala, 60 and Sudan. 61 One multicentre study involving 17 low-to middle-income countries included India, Pakistan, Colombia, Russia, China, Dominican Republic, Brazil, Argentina, El Salvador, Ukraine, Peru, Mexico, Belarus, Vietnam, Uganda, Guatemala, and Bangladesh.…”
Section: Epidemiology Of Perioperative Infections In High-income Counmentioning
confidence: 99%
“…61 One multicentre study involving 17 low-to middle-income countries included India, Pakistan, Colombia, Russia, China, Dominican Republic, Brazil, Argentina, El Salvador, Ukraine, Peru, Mexico, Belarus, Vietnam, Uganda, Guatemala, and Bangladesh. 62 There were five different study designs including one randomised controlled trial, 53 one non-randomised interventional before-after study, 62 16 cohort studies, [43][44][45][47][48][49][50]52,[54][55][56][57]59,60,63 one case-control study, 51 and three cross-sectional studies. 46,58,61 Most studies were conducted in children, with two in neonates 47,57 and two involving children and adult patients.…”
Section: Epidemiology Of Perioperative Infections In High-income Counmentioning
confidence: 99%
See 2 more Smart Citations